Методика обработки экспериментальных данных при моделировании дисперсии импеданса биологических тканей с помощью схемы замещения Фрике - Кривцун, И.В.; Пентегов, И.В.; Сидорец, В.Н.; Рымар, С.В. (Електротехніка і електромеханіка, 2017)
Разработана методика обработки экспериментальных данных для определения коэффициентов аппроксимации импеданса биологических тканей растительного и животного происхождения при моделировании дисперсии импеданса
с помощью схемы замещения Фрике. Проведен анализ свойств схемы замещения Фрике, ее возможностей и особенностей при моделировании дисперсии импеданса, резистанса и реактанса. Показано, что при нормировании дисперсии
активные составляющие импеданса для тканей растительного и животного происхождения подобны. Розроблено методику обробки експериментальних даних для визначення коефіцієнтів апроксимації імпедансу біологічних тканин рослинного й тваринного походження при моделюванні дисперсії імпедансу з допомогою схеми заміщення
Фріке. Проведено аналіз властивостей схеми заміщення Фріке, її можливостей і особливостей при моделюванні дисперсії імпедансу, резистансу й реактансу. Показано, що при нормуванні дисперсії активні складові імпедансу для тканин рослинного й тваринного походження подібні. Purpose. Modeling the dispersion of the biological tissue impedance of vegetable and animal origin using the Fricke equivalent
circuit; development of a technique for experimental data processing to determine the approximation coefficients of the dispersion of
the biological tissue impedance for this equivalent circuit; study of
the features of the equivalent circuit at modeling the dispersion of
the impedance, resistance, and reactance; the definition of the frequency domain in which using of the equivalent circuit is correct;
revealing and generalization of the main regularities of dissipation
of biological tissue impedance of vegetable and animal origin.
Methodology. The technique is based on the scientific provisions of
theoretical electrical engineering – the theory of the electromagnetic field in nonlinear media in modeling the dispersion of the
biological tissue impedance. Results. The electric circuit of the
Fricke equivalent circuit allows modeling the dependences of the
impedance module of biological tissues, active and reactive components of impedance with acceptable accuracy for practical purposes
in the frequency domain from 103
to 106
Hz. The equation of impedance of the Fricke equivalent circuit for biological tissues makes it
possible to approximate the frequency dependences of the impedance modulus, active and reactive parts of the total resistance only
by using the approximation coefficients corresponding to each part.
The developed method for determining the values of the approximation coefficients of the impedance equation for the Fricke equivalent
circuit for biological tissues allows to determine these values with
high accuracy for various biological tissues. It is shown that the
frequency dependences of the active component of the total resistance for tissues of vegetable and animal origin are similar. Originality. The developed technique operates with the normalized values
of the impedance modulus of the Fricke equivalent circuit, the active
and reactive components of the impedance as a function of frequency, which allows a comparative analysis of the dependencies of
these parameters of various biological tissues of plant and animal
origin. Practical value. The approximate dependences of the absolute impedance modulus, active and reactive components of the
impedance allow modeling processes occurring in biological tissues
with the passage of a current of different frequency. Dependence of
the impedance of biological tissue can be applied to the design of
diagnostic and control equipment to determine the properties of
tissues of animal and vegetable origin, including developing more
effective medical equipment.